SPP1+ tumor-associated macrophages define a high-risk subgroup and inform personalized therapy in hepatocellular carcinoma - Xu, Wei-Xuan; Ye, Ya-Mei; Chen, Jia-Lin; Guo, Xin-Ying; Li, Chen; Luo, Juan; Lu, Lin-Bin; Chen, Xiong (Frontiers in Oncology, 2025)
IntroductionRecently, contrary to attacking cancer cells, the tumor microenvironment (TME) with genomic stability and vulnerable nature has emerged as promising therapeutic targets in hepatocellular carcinoma (HCC). Within TME ecosystem, tumor-associated macrophages (TAMs) play a pivotal role in tumor evasion and progression of HCC. However, their clinical and therapeutic implications remain unexplored.MethodsUtilizing a large-scale sc-RNA seq dataset, a landscape of HCC cellular ecosystem was depicted. Based on previous literature, an effectively differential TAMs subset classification was identified. Gene variations was extracted through trajectory analysis and then unsupervised clustering was conducted within RNA-seq data. Subsequently, survival analysis, specific pathway enrichment as well as hub regulatory network analysis were performed. Additionally, the immune cell infiltration and genomic variations were evaluated between clusters. Drug sensitivity and underlying therapeutic molecular were also explored. Through multiple immunofluorescence, our findings were verified.ResultsHerein, integrating single-cell RNA sequencing (scRNA-seq) and bulk RNA-seq data, we established a novel TAM classification system based on mutually exclusive SPP1 and FOLR2 signatures. According to the TAM trajectory genes, unsupervised clustering stratified HCC into three distinct clusters. Cluster 3 (C3), which is characterized by metabolic dysregulation and immunosuppressive TME, exhibited the poorest prognosis among the three groups. Hub network analysis of C3 further indicated its characteristic dysregulation of liver-specific metabolism. SPP1 was identified as a key signature of C3, which contributed to suppressing the infiltration of CD8+ T cells. Therapeutic evaluation revealed that C3 were sensitive to chemotherapy and tyrosine kinase inhibitors, while those C1 and C2 were more suitable for immunotherapy. Drug screening identified potential therapeutic compounds for each cluster.ConclusionThis study redefines the heterogeneity of TAMs beyond the M1/M2 paradigm, linking the TAMs trajectory genes to HCC patient stratification. SPP1 blockade emerged as a strategy for counteracting immunosuppression, and cluster-specific therapies may optimize the management of HCC.